Problems in the Study of the Concepts of Underlying Categories - Faizova, Guzel R.; Sheremetyeva, Olga S.; Matveeva, Alfiya R. (Journal of History Culture and Art Research, 2017)
This paper considers the concepts of underlying categories. The economic good is one of such categories. In this regard, we considered such characteristics of an economic good as utility, value, and cost. The public goods, which are the goods that can benefit society and have two distinctive features, are an important category as well. In this regard, we characterized the characteristics and features of public goods and identified the main problems in this category. At present, the actual problem faced by the state is the production and evaluation of the effectiveness of public goods. The difficulty is that it is impossible to accurately determine the production volume of goods necessary for the society. Assessment of the effectiveness of the state activities requires the development of special tools. The existing legislatively defined methods have a number of shortcomings and do not allow obtaining an objective picture. Financing of most public goods occurs at the expense of the state, so it is very important to ensure and increase the efficiency of their spending at the moment. Public-private partnership is the most promising tool for better satisfying the needs of the population. The main goal of this work is to identify and discuss the main characteristics of the concepts of underlying categories and explain possible problems, issues faced by the state and the society.